Implementasi Alat Terapi Metode Gelombang Frekuensi Audiosonik Berbasis Kontrol Arduino Dengan Monitoring Osciloskop - Setiawan, Florentinus Budi; Wijaya, Hengky Adi; Pratomo, Leonardus Heru (Majalah Ilmiah Teknologi Elektro, 2022)
Abstract- The purpose of making this tool is to provide an alternative that can be used as a rehabilitation method for disease problems such as digestive, nervous and relaxation problems. In this present time, we need treatment facilities that can be done without face to face, to overcome these problems there is an audiosonic frequency type therapy device as an alternative in healing diseases in the field of rehabilitation. This therapy tool uses a frequency that can still be received by human hearing with a range of 20 – 20,000 Hz. How to use this therapy tool is to set the frequency you want to use and then listen to the sound produced by the therapy device. This therapy tool can be used while relaxing, reading or lying down and only takes 3 – 30 minutes. Keywords : therapy, audiosonic, sound, tool, disease, alternative